A low temperature curing polyester powder coating and a method for its preparation
By combining the melt esterification reaction of diols and diacids with organosilicon end-capping technology and triglycidyl isocyanurate, the problem of high-temperature curing of powder coatings was solved, and the technology of rapid curing and performance at low temperatures was realized.
Patent Information
- Application Number
- CN202510441242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-01-06
- Estimated Expiration
- 2045-04-09
AI Technical Summary
In existing technologies, powder coatings have high curing temperatures and long curing times, and it is difficult to achieve rapid curing at low temperatures. They also suffer from problems such as uneven coating, frosting, and poor mechanical properties.
Diols with different structures undergo a melt esterification reaction with diacids, followed by end-capping with a symmetrical organosilicon flexible monomer. The reaction of triglycidyl isocyanate with the terminal carboxyl groups of polyester resin is combined with end-capping accelerators and crosslinking curing agents to achieve low-temperature curing.
It achieves rapid curing at lower temperatures while maintaining good coating performance, improving the coating's water resistance, anti-blooming properties, and mechanical properties, thus meeting the needs of energy conservation, emission reduction, and improved production efficiency.
Smart Images

Figure BDA0005351108120000031 
Figure BDA0005351108120000032 
Figure BDA0005351108120000111
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder coating technology, specifically to a low-temperature curing polyester powder coating and its preparation method. Background Technology
[0002] Powder coatings are a new type of solid, environmentally friendly coating that differs from traditional solvent-based coatings. They are solid powdered synthetic resin coatings composed of solid resins, pigments, fillers, and additives. Because they do not use solvents, powder coatings are environmentally friendly, highly efficient, have low environmental requirements, and zero volatility, making them widely used in industries such as household appliances, pipeline corrosion protection, and automotive wheels. However, traditional thermosetting powder coatings require baking at 180-200℃ for 15-30 minutes to cure, which limits their application to heat-resistant metal substrates. Furthermore, the high-temperature operating environment during industrial production of powder coatings poses certain safety risks. Therefore, developing a low-temperature curing, high-performance powder coating has significant application value.
[0003] Polyester powder coatings are well-known thermosetting powder coatings, usually formulated with polyester resin and a curing agent. The baking temperature is generally between 180℃ and 200℃. If a catalyst is used to lower the baking temperature, several problems may occur: First, there is a risk of premature reaction in the extrusion process at 90℃-100℃; second, partial cross-linking before the powder is completely melted will lead to uneven film formation, resulting in poor appearance, orange peel, and ripples; in addition, there will be problems with low-temperature curing coatings frosting and haze.
[0004] Chinese patent CN116041676A discloses a polyester resin for low-temperature TGIC-cured powder coatings and its preparation method. The invention effectively improves the branching degree and end-carboxyl group activity of the polyester resin by using trihydroxyethyl isocyanurate monomer. It employs triglycidyl isocyanate (TGIC) as a curing agent and onium salt as a curing accelerator, achieving low-temperature curing performance of the polyester resin. The resulting polyester powder coating can be applied to equipment components exposed to the outdoors for extended periods, and the overall preparation process is simple. However, while the highly reactive monomers promote high-temperature curing of the resin, they often affect the system's room-temperature storage stability, resulting in technical problems such as poor mechanical properties, poor surface decoration, poor weather resistance, poor storage stability, and poor anti-frosting performance, causing significant inconvenience to industrial production.
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a low-temperature curing polyester powder coating and its preparation method. The method involves a melt esterification reaction between diols and diacids with different structures, followed by end-capping with a symmetrical organosilicon flexible monomer to improve the regularity and end-group activity of the resin. Simultaneously, the polyepoxy groups of triglycidyl isocyanate react with the terminal carboxyl groups of the polyester resin to achieve system curing. This results in a powder coating with good storage stability, anti-frosting properties, good hydrophobicity, and excellent mechanical properties. The coating can achieve rapid curing at relatively low temperatures while maintaining good film performance, thus meeting the needs of energy conservation, emission reduction, and improved production efficiency. Summary of the Invention
[0006] The technical problem solved by this invention is to provide a low-temperature curing polyester powder coating and its preparation method, which solves the problems of high curing temperature and long curing time of existing powder coatings.
[0007] The technical solution of this invention is:
[0008] A method for preparing a low-temperature curing polyester powder coating includes the following steps:
[0009] Step (1): Under a nitrogen atmosphere, add 30-40 parts by weight of neopentyl glycol, 5-8 parts by weight of 2-methyl-1,3-propanediol, 6-10 parts by weight of 1,6-hexanediol, 2-5 parts by weight of 1,4-cyclohexanediethanol, and 1-3 parts by weight of trimethylolpropane to the reaction flask. Stir and dissolve at 20-40 rpm. Then add 45-60 parts by weight of terephthalic acid, 4-8 parts by weight of adipic acid, 2-5 parts by weight of 1,4-cyclohexanedicarboxylic acid, and 1-3 parts by weight of m-phenylene oxide. Diformic acid and 0.5-2 parts of monobutyltin oxide are heated to 210-230℃ for esterification reaction for 1-3 hours (controlling the acid value at 20-30 mg (KOH) / g). 1-5 parts of end-capping accelerator are added and the reaction continues for 2-3 hours. The temperature is lowered to below 200℃, and 0.5-2 parts of solid accelerator and 0.1-0.3 parts of antioxidant are added. The mixture is stirred at 240-250℃ for 0.5-2 hours and discharged at room temperature to obtain a low-temperature curing polyester resin.
[0010] Step (2): By weight, mix 50-65 parts of low-temperature curing polyester resin, 3-8 parts of crosslinking curing agent, 0.5-2 parts of leveling agent 2020, 0.1-1 parts of brightening agent 701, 0.3-0.5 parts of benzoin, 10-16 parts of titanium dioxide and 16-20 parts of filler evenly, add them to a twin-screw extruder, melt-mix and extrude at 120-130℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain low-temperature curing polyester powder coating.
[0011] Furthermore, in step (1), the solid accelerator is ethyltriphenylphosphine bromide and the antioxidant is triphenyl phosphite.
[0012] Furthermore, in step (2), the crosslinking curing agent is triglycidyl isocyanurate.
[0013] Furthermore, in step (2), the filler is any one of barium sulfate, talc, or mica powder.
[0014] Furthermore, the preparation method of the end-capping accelerator in step (1) includes the following steps:
[0015] Step S1: Under a nitrogen atmosphere, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and solvent were added to a reaction flask. After stirring until homogeneous, trans-4-dimethylaminocrotonate was added. The reaction was carried out at 65-80℃ for 12-24 h. The mixture was separated by column chromatography (methanol / dichloromethane = 1:10), the organic phase was concentrated, and dried to obtain the organosilicon quaternary ammonium diacid monomer. The preparation reaction formula is as follows:
[0016]
[0017] Step S2: Under a nitrogen atmosphere, add organosilicon quaternary ammonium diacid monomer and methanol to a reaction flask. After stirring evenly, add imidazole and imidazole-based ionic liquid. React at 35-50℃ for 3-8 hours. Extract with ethyl acetate and deionized water, concentrate the organic phase, and separate by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, obtain the end-capping promoter. The preparation reaction formula is as follows:
[0018]
[0019] Furthermore, the solvent in step S1 is any one of acetonitrile, N,N-dimethylformamide, or 1,4-dioxane.
[0020] Furthermore, in step S1, the molar ratio of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and trans-4-dimethylaminocrotonate is 1:2.05-2.2.
[0021] Furthermore, in step S2, the molar ratio of organosilicon quaternary ammonium dicarboxylic acid monomer, imidazole, and imidazole-based ionic liquid is 1:2.1-2.3:0.02-0.04.
[0022] Furthermore, the preparation method of the imidazole-based ionic liquid in step S2 includes the following steps: 1 mol of N-methylimidazolium and 280 mL of ethyl acetate are added to a reaction flask, the temperature is slowly raised to 50 °C, 1.1 mol of n-butane bromide is added dropwise, and the mixture is stirred and refluxed at 70 °C for 24 h. After cooling to room temperature, ethyl acetate and deionized water are separated, the organic phase is concentrated, and dried to obtain the imidazole-based ionic liquid.
[0023] The beneficial technical effects of this invention are:
[0024] Compared with existing technologies, this invention prepares a capping accelerator containing flexible organosilicon and imidazole through quaternization and Michael addition reactions using 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, trans-4-dimethylaminocrotonate, imidazole, etc. A melt esterification reaction is then performed between diols with different structures and diacids, followed by capping with the capping accelerator to improve the regularity and end-group activity of the resin. Simultaneously, the polyepoxy groups of triglycidyl isocyanate react with the terminal carboxyl groups of the polyester resin to achieve system curing. The resin is then uniformly mixed with pigments, fillers, and additives to obtain a low-temperature curing polyester resin. This coating can achieve rapid curing at lower temperatures while maintaining good film performance, thus meeting the needs of energy conservation, emission reduction, and improved production efficiency.
[0025] (1) Excellent water resistance and high curing degree: The end-capping curing agent contains low surface energy organosilicon groups with good symmetry, which increases the flexibility of the molecular chain. The coating is arranged more tightly during the crystallization process, making it difficult for water molecules to enter the interior of the coating, thus enhancing the water resistance of the coating. Organosilicon itself has excellent flexibility and elasticity. When it is added to polyester powder coating, it can significantly improve the flexibility of the coating, enabling the coating to achieve good curing effect at a lower temperature. At the same time, the imidazole and quaternary ammonium salt in the end-capping curing agent can interact with the epoxy functional groups in polyester resin and triglycidyl isocyanate (i.e., crosslinking curing agent), catalyzing and accelerating the crosslinking reaction between polyester resin and curing agent, so that the reaction can proceed more rapidly and completely at a lower temperature. The principle is that the tertiary nitrogen atoms in imidazole and quaternary ammonium salt have catalytic activity and can promote the ring-opening polymerization of epoxy groups.
[0026] (2) Excellent anti-frosting performance and adhesion: The low surface tension and low surface energy of silicone help improve the surface properties of the coating, making it easier for the coating to form a uniform and smooth coating, thereby reducing the occurrence of frosting. At the same time, the addition of silicone improves the flexibility of the coating, enabling it to better adapt to the deformation and displacement of the substrate, thereby maintaining a tight bond between the coating and the substrate and helping to enhance the adhesion between the coating and the substrate.
[0027] (3) Better mechanical properties: During the coating curing process, the end-capping accelerator can chemically crosslink with the crosslinking curing agent to form a highly ordered layered structure. At the same time, the organosilicon itself has excellent flexibility and elasticity, which enables the coating to better resist the generation and propagation of cracks when subjected to external forces, and avoids damage to the coating when subjected to impact, thereby improving the overall strength and durability of the coating. Detailed Implementation
[0028] The present invention is further illustrated below by way of examples, but these examples do not limit the invention to the scope of the embodiments described. Experimental methods not specifically described in the following examples were performed according to conventional methods and conditions, or as selected according to the product instructions. Unless otherwise stated, the raw materials and reagents used in this application are commercially available products or can be prepared by known methods.
[0029] Preparation method of imidazole ionic liquid: Add 1 mol of N-methylimidazolium and 280 mL of ethyl acetate to a reaction flask, slowly heat to 50 °C, add 1.1 mol of n-bromobutane dropwise, stir and reflux at 70 °C for 24 h, cool to room temperature, separate ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain imidazole ionic liquid.
[0030] 1,3-Bis(chloromethyl)-1,1,3,3-Tetramethyldisiloxane, CAS No. 2362-10-9.
[0031] Trans-4-dimethylaminocrotonate, CAS number 848133-35-7.
[0032] Imidazole, CAS number 288-32-4.
[0033] Example 1
[0034] (1) Under a nitrogen atmosphere, 35 mmol of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 160 mL of acetonitrile were added to a reaction flask. After stirring evenly, 73.5 mmol of trans-4-dimethylaminocrotonate was added. The reaction was carried out at 75 °C for 15 h. The reaction was separated by column chromatography (methanol / dichloromethane = 1:10). The organic phase was concentrated and dried to obtain organosilicon quaternary ammonium dicarboxylic acid monomer.
[0035] (2) Under a nitrogen atmosphere, 30 mmol of organosilicon quaternary ammonium salt diacid monomer and 300 mL of methanol were added to the reaction flask. After stirring evenly, 66 mmol of imidazole and 0.9 mmol of imidazole ionic liquid were added. The reaction was carried out at 45 °C for 6 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping promoter was obtained.
[0036] (3) Under a nitrogen atmosphere, add 35g neopentyl glycol, 6g 2-methyl-1,3-propanediol, 8g 1,6-hexanediol, 4g 1,4-cyclohexanediol, and 2g trimethylolpropane to a reaction flask and stir to dissolve. Add 50g terephthalic acid, 7g adipic acid, 3g 1,4-cyclohexanedicarboxylic acid, 2g isophthalic acid, and 1.5g monobutyltin oxide. Heat to 220℃ for esterification reaction for 2h (control the acid value at 20-30mg(KOH) / g). Add 1g end-capping accelerator and continue the reaction for 2h. Cool down to below 200℃ and add 1g ethyltriphenylphosphine bromide and 0.2g triphenyl phosphite. Stir at 245℃ for 1h and discharge at room temperature to obtain a low-temperature curing polyester resin.
[0037] (4) Mix 50g of low-temperature curing polyester resin, 5g of crosslinking curing agent, 1.2g of leveling agent 2020, 0.5g of brightening agent 701, 0.4g of benzoin, 13g of titanium dioxide and 18g of barium sulfate evenly, add them to a twin-screw extruder, melt-mix and extrude at 125℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain a low-temperature curing polyester powder coating.
[0038] Example 2
[0039] (1) Under a nitrogen atmosphere, 80 mmol of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 240 mL of N,N-dimethylformamide were added to a reaction flask. After stirring evenly, 164 mmol of trans-4-dimethylaminocrotonate was added. The reaction was carried out at 80 °C for 12 h. The mixture was separated by column chromatography (methanol / dichloromethane = 1:10), the organic phase was concentrated, and dried to obtain organosilicon quaternary ammonium dicarboxylic acid monomer.
[0040] (2) Under a nitrogen atmosphere, 70 mmol of organosilicon quaternary ammonium salt diacid monomer and 560 mL of methanol were added to the reaction flask. After stirring evenly, 147 mmol of imidazole and 1.4 mmol of imidazole ionic liquid were added. The reaction was carried out at 50 °C for 3 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping promoter was obtained.
[0041] (3) Under a nitrogen atmosphere, add 30g neopentyl glycol, 5g 2-methyl-1,3-propanediol, 6g 1,6-hexanediol, 2g 1,4-cyclohexanediethanol, and 1g trimethylolpropane to a reaction flask and stir to dissolve. Add 45g terephthalic acid, 4g adipic acid, 2g 1,4-cyclohexanedicarboxylic acid, 1g isophthalic acid, and 0.5g monobutyltin oxide. Heat to 230℃ for esterification reaction for 1h (control the acid value at 20-30mg(KOH) / g). Add 2g end-capping accelerator and continue the reaction for 2h. Cool down to below 200℃ and add 0.5g ethyltriphenylphosphine bromide and 0.1g triphenyl phosphite. Stir at 250℃ for 0.5h and discharge at room temperature to obtain a low-temperature curing polyester resin.
[0042] (4) Mix 54g of low-temperature curing polyester resin, 3g of crosslinking curing agent, 0.5g of leveling agent 2020, 0.1g of brightening agent 701, 0.3g of benzoin, 10g of titanium dioxide and 20g of barium sulfate evenly, add them to a twin-screw extruder, melt-mix and extrude at 130℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain a low-temperature curing polyester powder coating.
[0043] Example 3
[0044] (1) Under a nitrogen atmosphere, 50 mmol of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 300 mL of 1,4-dioxane were added to a reaction flask and stirred until homogeneous. Then, 110 mmol of trans-4-dimethylaminocrotonate was added and reacted at 65 °C for 24 h. The mixture was separated by column chromatography (methanol / dichloromethane = 1:10), the organic phase was concentrated, and dried to obtain the organosilicon quaternary ammonium dicarboxylic acid monomer.
[0045] (2) Under a nitrogen atmosphere, 40 mmol of organosilicon quaternary ammonium salt diacid monomer and 480 mL of methanol were added to the reaction flask. After stirring evenly, 92 mmol of imidazole and 1.6 mmol of imidazole ionic liquid were added. The reaction was carried out at 35 °C for 8 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping promoter was obtained.
[0046] (3) Under a nitrogen atmosphere, add 40g neopentyl glycol, 8g 2-methyl-1,3-propanediol, 10g 1,6-hexanediol, 5g 1,4-cyclohexanediethanol and 3g trimethylolpropane to a reaction flask and stir to dissolve. Add 60g terephthalic acid, 8g adipic acid, 5g 1,4-cyclohexanedicarboxylic acid, 3g isophthalic acid and 2g monobutyltin oxide. Heat to 210℃ for esterification reaction for 3h (control the acid value at 20-30mg(KOH) / g). Add 3g end-capping accelerator and continue the reaction for 3h. Cool down to below 200℃ and add 2g ethyltriphenylphosphine bromide and 0.3g triphenyl phosphite. Stir at 240℃ for 2h and discharge at room temperature to obtain a low-temperature curing polyester resin.
[0047] (4) Mix 58g of low-temperature curing polyester resin, 8g of crosslinking curing agent, 2g of leveling agent 2020, 1g of brightening agent 701, 0.5g of benzoin, 16g of titanium dioxide and 16g of mica powder evenly, add them to a twin-screw extruder, melt-mix and extrude at 120℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain a low-temperature curing polyester powder coating.
[0048] Example 4
[0049] (1) Under a nitrogen atmosphere, 120 mmol of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 600 mL of acetonitrile were added to a reaction flask. After stirring evenly, 255 mmol of trans-4-dimethylaminocrotonate was added. The reaction was carried out at 75 °C for 15 h. The reaction was separated by column chromatography (methanol / dichloromethane = 1:10). The organic phase was concentrated and dried to obtain organosilicon quaternary ammonium dicarboxylic acid monomer.
[0050] (2) Under a nitrogen atmosphere, 100 mmol of organosilicon quaternary ammonium salt diacid monomer and 950 mL of methanol were added to the reaction flask. After stirring evenly, 225 mmol of imidazole and 3.2 mmol of imidazole ionic liquid were added. The reaction was carried out at 45 °C for 6 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping promoter was obtained.
[0051] (3) Under a nitrogen atmosphere, add 36g neopentyl glycol, 8g 2-methyl-1,3-propanediol, 9g 1,6-hexanediol, 3g 1,4-cyclohexanediethanol, and 2g trimethylolpropane to a reaction flask and stir to dissolve. Add 52g terephthalic acid, 8g adipic acid, 4g 1,4-cyclohexanedicarboxylic acid, 2g isophthalic acid, and 1.5g monobutyltin oxide. Heat to 225℃ for esterification reaction for 3h (control the acid value at 20-30mg(KOH) / g). Add 4g end-capping accelerator and continue the reaction for 2h. Cool down to below 200℃ and add 1.6g ethyltriphenylphosphine bromide and 0.2g triphenyl phosphite. Stir at 245℃ for 1h and discharge at room temperature to obtain a low-temperature curing polyester resin.
[0052] (4) Mix 62g of low-temperature curing polyester resin, 5g of crosslinking curing agent, 1g of leveling agent 2020, 0.8g of brightening agent 701, 0.45g of benzoin, 15g of titanium dioxide and 17g of barium sulfate evenly, add them to a twin-screw extruder, melt-mix and extrude at 130℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain a low-temperature curing polyester powder coating.
[0053] Example 5
[0054] (1) Under a nitrogen atmosphere, 30 mmol of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 135 mL of N,N-dimethylformamide were added to a reaction flask and stirred until homogeneous. Then, 63 mmol of trans-4-dimethylaminocrotonate was added and the reaction was carried out at 70 °C for 24 h. The reaction was separated by column chromatography (methanol / dichloromethane = 1:10), the organic phase was concentrated and dried to obtain organosilicon quaternary ammonium dicarboxylic acid monomer.
[0055] (2) Under a nitrogen atmosphere, 25 mmol of organosilicon quaternary ammonium salt dicarboxylic acid monomer and 265 mL of methanol were added to the reaction flask. After stirring evenly, 56 mmol of imidazole and 0.7 mmol of imidazole ionic liquid were added. The reaction was carried out at 40 °C for 6 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping promoter was obtained.
[0056] (3) Under a nitrogen atmosphere, add 36g neopentyl glycol, 6g 2-methyl-1,3-propanediol, 10g 1,6-hexanediol, 3g 1,4-cyclohexanediethanol and 2g trimethylolpropane to a reaction flask and stir to dissolve. Add 55g terephthalic acid, 5g adipic acid, 4g 1,4-cyclohexanedicarboxylic acid, 2g isophthalic acid and 2g monobutyltin oxide. Heat to 225℃ for esterification reaction for 2h (control the acid value at 20-30mg(KOH) / g). Add 5g end-capping accelerator and continue the reaction for 3h. Cool down to below 200℃ and add 1.5g ethyltriphenylphosphine bromide and 0.3g triphenyl phosphite. Stir at 250℃ for 2h and discharge at room temperature to obtain a low-temperature curing polyester resin.
[0057] (4) Mix 65g of low-temperature curing polyester resin, 5g of crosslinking curing agent, 1g of leveling agent 2020, 0.6g of brightening agent 701, 0.4g of benzoin, 15g of titanium dioxide and 20g of talc evenly, add them to a twin-screw extruder, melt-mix and extrude at 125℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain a low-temperature curing polyester powder coating.
[0058] Comparative Example 1
[0059] (1) Under a nitrogen atmosphere, 35g of neopentyl glycol, 6g of 2-methyl-1,3-propanediol, 8g of 1,6-hexanediol, 4g of 1,4-cyclohexanediethanol and 2g of trimethylolpropane were added to a reaction flask and stirred at 30 rpm to dissolve. Then, 50g of terephthalic acid, 7g of adipic acid, 3g of 1,4-cyclohexanedicarboxylic acid, 2g of isophthalic acid and 1.5g of monobutyltin oxide were added. The temperature was raised to 220℃ for esterification reaction for 2h (the acid value was controlled at 20-30mg(KOH) / g). Then, 1g of organosilicon quaternary ammonium diacid monomer (prepared from Example 1) was added and the reaction was continued for 2h. The temperature was lowered to below 200℃ and 1g of ethyltriphenylphosphine bromide and 0.2g of triphenyl phosphite were added. The mixture was stirred at 245℃ for 1h and discharged at room temperature to obtain the modified polyester resin.
[0060] (2) Mix 50g of modified polyester resin, 5g of crosslinking curing agent, 1.2g of leveling agent 2020, 0.5g of brightening agent 701, 0.4g of benzoin, 13g of titanium dioxide and 18g of barium sulfate evenly, add them to a twin-screw extruder, melt-mix and extrude at 125℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain polyester powder coating.
[0061] Comparative Example 2
[0062] (2) Under a nitrogen atmosphere, 30 mmol of 2,4-hexadienoic acid (structural formula: [insert structural formula here]) was added to the reaction flask. The CAS number is 3588-17-8. After stirring with 300 mL of methanol, 66 mmol of imidazole and 0.9 mmol of imidazole-based ionic liquid were added. The mixture was reacted at 45 °C for 6 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and separated by column chromatography (ethyl acetate / n-heptane = 1:3). After drying, the end-capping agent was obtained.
[0063] (2) Under a nitrogen atmosphere, 35g of neopentyl glycol, 6g of 2-methyl-1,3-propanediol, 8g of 1,6-hexanediol, 4g of 1,4-cyclohexanediethanol, and 2g of trimethylolpropane were added to a reaction flask and stirred at 30 rpm to dissolve. Then, 50g of terephthalic acid, 7g of adipic acid, 3g of 1,4-cyclohexanedicarboxylic acid, 2g of isophthalic acid, and 1.5g of monobutyltin oxide were added. The temperature was raised to 220℃ for esterification reaction for 2h (the acid value was controlled at 20-30mg(KOH) / g). 1g of end-capping agent was added and the reaction continued for 2h. The temperature was lowered to below 200℃, and 1g of ethyltriphenylphosphine bromide and 0.2g of triphenyl phosphite were added. The mixture was stirred at 245℃ for 1h and discharged at room temperature to obtain the modified polyester resin.
[0064] (3) Mix 50g of low-temperature curing polyester resin, 5g of crosslinking curing agent, 1.2g of leveling agent 2020, 0.5g of brightening agent 701, 0.4g of benzoin, 13g of titanium dioxide and 18g of barium sulfate evenly, add them to a twin-screw extruder, melt-mix and extrude at 125℃, press and cool with a double roller, grind with a high-speed grinding mill, and sieve to obtain polyester powder coating.
[0065] Comparative Example 3
[0066] (1) Under a nitrogen atmosphere, 35g of neopentyl glycol, 6g of 2-methyl-1,3-propanediol, 8g of 1,6-hexanediol, 4g of 1,4-cyclohexanediethanol and 2g of trimethylolpropane were added to a reaction flask and stirred at 30 rpm to dissolve. Then, 50g of terephthalic acid, 7g of adipic acid, 3g of 1,4-cyclohexanedicarboxylic acid, 2g of isophthalic acid and 1.5g of monobutyltin oxide were added. The temperature was raised to 220℃ for esterification reaction for 2h (controlling the acid value at 20-30mg(KOH) / g). The temperature was lowered to below 200℃, and 1g of ethyltriphenylphosphine bromide and 0.2g of triphenyl phosphite were added. The mixture was stirred at 245℃ for 1h and discharged at room temperature to obtain polyester resin.
[0067] (2) Mix 50g polyester resin, 5g crosslinking curing agent, 1.2g leveling agent 2020, 0.5g gloss enhancer 701, 0.4g benzoin, 13g titanium dioxide and 18g barium sulfate evenly, add to twin-screw extruder, melt and knead at 125℃, extrude, press into sheets by double rollers, cool, grind with a high-speed grinding mill, and sieve to obtain polyester powder coating.
[0068] Preparation of the coating to be tested: Low-temperature curing polyester powder coating is electrostatically sprayed onto the surface of the substrate and baked at 150℃ for 10 min to obtain the coating to be tested.
[0069] Contact angle test: A contact angle measuring instrument was used, with a droplet size of 5μL. Five parallel measurements were taken and the average value was recorded.
[0070] Curing degree test: Nitrogen atmosphere, temperature range 20-200℃, heating rate 20℃ / min. The curing degree of the coating is tested according to GB / T19466.2-2004 standard. Curing degree (%) = (ΔH0 - ΔH) c ) / △H0×100%. Where △H0 is the enthalpy change (J / g) measured when the coating is fully cured, and △H c The enthalpy change (J / g) is the value of the coating after baking and curing at 150℃ for 10 min.
[0071] Table 1 Water resistance and curing degree test
[0072]
[0073]
[0074] The test results in the table above show that the water resistance and curing degree of polyester powder coatings are significantly improved with the increase of end-capping curing agent content. In Example 4, the contact angle is 113.05° and the curing degree is 98.41%, indicating a significant improvement in the water resistance of the prepared coating. This is because the end-capping curing agent contains low surface energy organosilicon groups with good symmetry, which increases the flexibility of the molecular chains. During the crystallization process, the coating is more tightly packed, making it difficult for water molecules to penetrate the coating interior, thus enhancing its water resistance. Secondly, organosilicon itself has excellent flexibility. Its properties and elasticity, when added to polyester powder coatings, can significantly improve the flexibility of the coating, allowing it to achieve good curing results at lower temperatures. Simultaneously, the imidazole and quaternary ammonium salts in the end-capping curing agent can interact with the epoxy functional groups in the polyester resin and triglycidyl isocyanate (i.e., the crosslinking curing agent), catalyzing and accelerating the crosslinking reaction between the polyester resin and the curing agent. This allows the reaction to proceed more rapidly and completely at lower temperatures. The principle is that the tertiary nitrogen atoms in the imidazole and quaternary ammonium salts have catalytic activity, promoting the ring-opening polymerization of epoxy groups. Comparative Example 1, lacking an imidazole structure, has poor curing degree; Comparative Example 2, lacking both organosilicon and quaternary ammonium salt structures, has poor curing performance at low temperatures; and Comparative Example 3, a common unmodified polyester resin, has the worst performance.
[0075] Low-temperature baking anti-blooming performance test: After curing, the coating is placed in an oven at 130℃ for 2 hours and then cooled. The gloss of the coating is measured and the gloss retention rate is calculated. The lower the gloss retention rate, the worse the anti-blooming performance. Gloss retention rate (%) = A1 / A0×100%, where A1 is the gloss of the coating after the baking test and A0 is the gloss of the original coating. The gloss test method is as follows: the gloss is tested using a gloss meter according to GB / T 8941-2013 "Determination of specular gloss of paper and paperboard".
[0076] Adhesion test: Tested according to GB / T 9286-2021 "Paints and Varnishes Cross-cut Test".
[0077] Table 2. Gloss retention and adhesion tests
[0078] Gloss retention rate / % Adhesion / Grade Example 1 75.06 1 Example 2 81.54 0 Example 3 88.61 0 Example 4 93.25 0 Example 5 94.30 0 Comparative Example 1 62.15 2 Comparative Example 2 60.82 2 Comparative Example 3 53.65 3
[0079] As can be seen from the test results in the table above, the polyester powder coating in Example 5 has good anti-frosting performance, with a gloss retention rate as high as 94.30% and an adhesion grade of 0, indicating that the coating and the substrate have good adhesion. This may be because, with the increase of the end-capping curing agent content, the low surface tension and low surface energy characteristics of organosilicon help improve the surface properties of the coating, making it easier for the coating to form a uniform and smooth coating, thereby reducing the occurrence of frosting. At the same time, the addition of organosilicon improves the flexibility of the coating, enabling it to better adapt to the deformation and displacement of the substrate, thereby maintaining a tight bond between the coating and the substrate and helping to enhance the adhesion between the coating and the substrate.
[0080] Impact resistance test: conducted according to the method in standard GB / T 1732-2020 "Determination of Impact Resistance of Coating Film".
[0081] Hardness test: The test was conducted according to the method in GB / T 6739-2006 "Determination of Hardness of Paint Film by Pencil Method".
[0082] Table 3 Impact resistance and hardness test
[0083]
[0084]
[0085] A higher hardness rating indicates a stronger ability of the coating film to resist the indentation of hard objects on its surface. As can be seen from the test results in the table above, all the examples exhibit high hardness. The reason for this result may be that during the coating curing process, the end-capping accelerator can chemically crosslink with the crosslinking curing agent to form a highly ordered layered structure. At the same time, the organosilicon itself has excellent flexibility and elasticity, which allows the coating to better resist the generation and propagation of cracks when subjected to external forces, preventing the coating from breaking when subjected to impact, thereby improving the overall strength and durability of the coating.
[0086] This invention can be summarized in other specific forms that do not depart from the spirit or main features of the invention. The above embodiments of the invention are merely illustrative and not restrictive. Therefore, any minor modifications, equivalent changes, or alterations made to the above embodiments based on the essential technology, composition, or content of the invention fall within the scope of the invention.
Claims
1. A process for the preparation of a low temperature curing polyester powder coating, characterized in that, The preparation method comprises the following steps: Step (1), under a nitrogen atmosphere, 30-40 parts of neopentyl glycol, 5-8 parts of 2-methyl-1, 3-propanediol, 6-10 parts of 1, 6-hexanediol, 2-5 parts of 1, 4-cyclohexane dimethanol, 1-3 parts of trimethylolpropane are added into a reaction flask, and dissolved under stirring at 20-40 rpm, 45-60 parts of terephthalic acid, 4-8 parts of adipic acid, 2-5 parts of 1, 4-cyclohexane dicarboxylic acid, 1-3 parts of isophthalic acid and 0.5-2 parts of monobutyl tin oxide are added, and esterification is carried out at 210-230 DEG C for 1-3 h, 1-5 parts of a capping promoter is added and the reaction is continued for 2-3 h, the temperature is lowered to below 200 DEG C, 0.5-2 parts of a solid promoter and 0.1-0.3 parts of an antioxidant are added, and stirring is carried out at 240-250 DEG C for 0.5-2 h, and the product is discharged at room temperature to obtain a low-temperature curing polyester resin; Step (2), 50-65 parts of the low-temperature curing polyester resin, 3-8 parts of a cross-linking curing agent, 0.5-2 parts of a leveling agent, 0.1-1 parts of a gloss enhancer, 0.3-0.5 parts of benzoin, 10-16 parts of titanium white and 16-20 parts of a filler are uniformly mixed according to parts by weight, and then added into a double-screw extruder, and melt-kneaded and extruded at 120-130 DEG C, and then crushed by a high-speed grinding machine after being pressed into a sheet by a double-roller and cooled, and sieved to obtain a low-temperature curing polyester powder coating; The preparation method of the capping promoter in step (1) comprises the following steps: Step S1, under a nitrogen atmosphere, 1, 3-bis (chloromethyl) -1, 1, 3, 3-tetramethyldisiloxane and a solvent are added into a reaction flask, stirred uniformly, and then trans-4-dimethylamino crotonic acid hydrochloride is added, and the reaction is carried out at 65-80 DEG C for 12-24 h, and then column chromatography is carried out, the organic phase is concentrated, and dried to obtain a silicone quaternary ammonium salt diacid monomer; Step S2, under a nitrogen atmosphere, the silicone quaternary ammonium salt diacid monomer and methanol are added into a reaction flask, stirred uniformly, and then imidazole and imidazole-based ionic liquid are added, and the reaction is carried out at 35-50 DEG C for 3-8 h, and then ethyl acetate and deionized water are added for extraction, the organic phase is concentrated, column chromatography is carried out, and dried to obtain a capping promoter.
2. The process for the preparation of a low temperature curing polyester powder coating according to claim 1, characterized in that, The solid promoter in step (1) is ethyl triphenyl phosphonium bromide, and the antioxidant is triphenyl phosphite.
3. The process for the preparation of a low temperature curing polyester powder coating according to claim 1, characterized in that, The cross-linking curing agent in step (2) is isocyanuric acid triglycidyl ester.
4. The process for the preparation of a low temperature curing polyester powder coating according to claim 1, characterized in that, The filler in step (2) is any one of barium sulfate, talcum powder or mica powder.
5. The process for the preparation of a low temperature solidifying polyester powder coating according to claim 1, characterized in that, The solvent in step S1 is any one of acetonitrile, N, N-dimethylformamide or 1, 4-dioxane.
6. The process for the preparation of a low temperature solidifying polyester powder coating according to claim 1, characterized in that, The molar ratio of 1, 3-bis (chloromethyl) -1, 1, 3, 3-tetramethyldisiloxane to trans-4-dimethylamino crotonic acid hydrochloride in step S1 is 1:2.05-2.
2.
7. The process for the preparation of a low temperature solidifying polyester powder coating according to claim 1, characterized in that, The molar ratio of the silicone quaternary ammonium salt diacid monomer to imidazole to imidazole-based ionic liquid in step S2 is 1:2.1-2.3:0.02-0.
04.
8. The process for the preparation of a low temperature solidifying polyester powder coating according to claim 1, characterized in that, The preparation method of the imidazole-based ionic liquid in the step S2 comprises the following steps: adding 1 mol of N-methyl imidazole and 280 mL of ethyl acetate into a reaction flask, slowly heating to 50 DEG C, adding 1.1 mol of n-bromobutane dropwise, stirring at 70 DEG C under reflux for 24 h, cooling to room temperature, separating the ethyl acetate and deionized water, concentrating the organic phase, and drying to obtain the imidazole-based ionic liquid.
9. A low temperature curing polyester powder coating, characterized in that, The preparation method of any one of claims 1-8.
Citation Information
Patent Citations
Polyester resin for low-temperature TGIC (triglycidyl isocyanurate) curing powder coating and preparation method of polyester resin
CN116041676A
Method for preparing ultralow temperature curing resin
CN106085157A